Counter-storying the grand narrative of science (teacher) education: Towards culturally responsive teaching - Taylor, Peter (Springer, 2011)
John Settlage’s article—Counterstories from White Mainstream Preservice Teachers: Resisting the Master Narrative of Deficit by Default—outlines his endeavour to enable pre-service teachers to develop culturally responsive science teaching identities for resisting the master narrative of deficit thinking when confronted by the culturally different ‘other.’ Case study results are presented of the role of counterstories in enabling five pre-service teachers to overcome deficit thinking. In this forum, Philip Moore, a cultural anthropologist and university professor, deepens our understanding of the power and significance of counterstories as an educational tool for enabling students to deconstruct oppressive master narratives. Jill Slay, dean of a science faculty, examines her own master narrative about the compatibility of culturally similar academics and graduate students, and finds it lacking. But first, I introduce this scholarship with background notes on the critical paradigm and its adversary, the grand narrative of science education, following which I give an appreciative understanding of John’s pedagogical use of counterstories as a transformative strategy for multi-worldview science teacher education.